Spatiotemporal Dynamics and Mechanisms of Coastal Rural Settlements Under Diverse Geomorphic Conditions: A Multi-Bay Analysis in Guangdong, China - Ying Pan; Siyi Feng; Ying Shi (Land)
The spatiotemporal evolution of coastal rural settlements varies significantly across different geomorphic environments, yet this variation is underexplored in current research. Guided by Coupled Human and Natural Systems, this study examines the adaptation mechanisms between coastal rural settlements and landforms using an integrated framework that combines various bay types, spatiotemporal characteristics, and dynamic drivers. Four representative bay types along Guangdong’s coast were analyzed: Hilly Ria Coast, Platform Ria Coast, Barrier-Lagoon Coast, and Estuarine Delta Coast. Using multi-source remote sensing data and optimized Geodetector modeling (1972 vs. 2022), we identified the patterns of spatiotemporal evolution and their driving forces. The results reveal distinct adaptation pathways: Hilly Ria Coast settlements expanded in a constrained manner, supported by tunnel–bridge infrastructure; Platform Ria Coasts developed multi-nucleated, port-oriented clusters through harbor-linked road networks; Barrier-Lagoon Coasts achieved balanced growth through integrated land–river–sea governance; and Estuarine Delta Coasts experienced urban–rural restructuring accompanied by water network degradation. This study proposes governance strategies tailored to specific landforms to support sustainable coastal planning.